2012
DOI: 10.1007/s00262-012-1319-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of a multi-epitope-pulsed dendritic cell vaccine for patients with newly diagnosed glioblastoma

Abstract: BackgroundThis study evaluated the safety and immune responses to an autologous dendritic cell vaccine pulsed with class I peptides from tumor-associated antigens (TAA) expressed on gliomas and overexpressed in their cancer stem cell population (ICT-107).MethodsTAA epitopes included HER2, TRP-2, gp100, MAGE-1, IL13Rα2, and AIM-2. HLA-A1- and/or HLA-A2-positive patients with glioblastoma (GBM) were eligible. Mononuclear cells from leukapheresis were differentiated into dendritic cells, pulsed with TAA peptides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
252
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(265 citation statements)
references
References 27 publications
1
252
0
3
Order By: Relevance
“…In an animal study conducted by Xu et al 104 in 2009, a dendritic cell vaccine was created against tumor-associated antigens specific to CSCs. The results showed that such 77 who used vaccines that targeted tumor antigens highly specific to CSCs. The vaccine developed was nontoxic, and for the 16 patients who received it, the median progression-free survival (PFS) time was 16.9 months and the median OS time was 38.4 months.…”
Section: Ongoing and Previous Clinical Trialsmentioning
confidence: 92%
“…In an animal study conducted by Xu et al 104 in 2009, a dendritic cell vaccine was created against tumor-associated antigens specific to CSCs. The results showed that such 77 who used vaccines that targeted tumor antigens highly specific to CSCs. The vaccine developed was nontoxic, and for the 16 patients who received it, the median progression-free survival (PFS) time was 16.9 months and the median OS time was 38.4 months.…”
Section: Ongoing and Previous Clinical Trialsmentioning
confidence: 92%
“…These strategies were evaluated in early-phase clinical trials in newly-diagnosed GBM (111)(112)(113)(114). DC vaccine loaded with autologous tumor lysate was examined in a phase I clinical trial with 56 patients with relapsed GBM, resulting in a median PFS of 3 months and median OS of 9.6 months, with 2-year OS of 14.8% (115).…”
Section: Immunotherapy Of Gbmmentioning
confidence: 99%
“…More recently, dendritic cell immunotherapy using multiple epitopes has also been reported in the treatment of brain tumors. 45 Finally, we should consider how we apply immune checkpoint inhibitors in the field of lung cancer. Combination with chemotherapy, molecular-targeted therapy, and other vaccine therapies could be promising choices.…”
Section: Future Perspectivesmentioning
confidence: 99%